Modelagem matemática da variação espaço-temporal da temperatura média diária e do ciclo do algodoeiro herbáceo no Estado de Goiás - ANTONINI, Jorge Cesar dos Anjos (2009)
The regional climatic conditions in the State of Goias Brazil are favorable for herbaceous cotton (Gossypium hirsutum L. r. latifolium hutch) cultivation. However, for achieving the best productivities, it is important that both the planting date and the fruiting period be matched with the adequate soil-water availability as well as that the period from open bull to harvesting be coincident with the dry period. Thus, the knowledge of cotton cycle as function of planting location is very important for choosing the optimum planting date. In this context, the air temperature is one of the climatic variables that mostly influence the cotton growth. Nevertheless, the low density of meteorological stations with capability for measuring temperature has restricted the modeling studies for estimating cotton cycle. This work was carried out with the objective of developing and validating mathematical models to estimate average daily air temperature and based on the degreesday theory, the cycle of herbaceous cotton in the State of Goias, considering altogether its variations in space and time. Both models were based on a linear combination of elevation, latitude, longitude, and the daily time variation, represented by an incomplete Fourier series. The parameter models were adjusted to the data from 21 meteorological stations available in the State of Goiás and Federal District of Brazil, using multiple linear regressions with observations varying from eight to twenty four years. In the case of modeling degrees-day, the maximum and minimum temperature data were limited between 15°C and 40°C, which were taken as the lower and upper threshold temperatures, respectively. The air-temperature model was validated against the measured data from three meteorological stations from different elevations: high (1100 m), medium (554 m) and low (431 m). The coefficients of determination obtained from fitting the models for both daily air-temperature and daily degrees-day were 0.82 and 0.84, respectively, resulting in a medium performance for both low and high altitudes and very good for intermediate altitudes. The validation of the degrees-day model was conducted by comparing the period duration running from crop emergence to 90% open bulls observed from cotton cultivars, cropped in commercial fields. The results showed an overall performance index of 0.85, which was considered as very good. The models developed in this study adequately estimated the average daily air temperature and the cycle of herbaceous cotton cultivars in the State of Goias